Development of A Teaching Module Containing Islamic Values on the Material of the Human Reproductive System to Strengthen Students’ Critical Thinking Abilities in Madrasah Aliyah - Tyas Khofilla; Priyantini Widiyaningrum; Dyah Rini Indriyanti; Andin Irsadi (Universitas Negeri Semarang, 2025)
The purpose of this research is to develop and implementation of a teaching module containing Islamic values on the human reproductive system material to improve critical thinking. The development research method used ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Data were obtained analysis, questionnaires, and tests (pre-post). The module was analyzed by expert validators. Data analysis techniques used descriptive analysis and statistical analysis. The results of the study showed that the characteristics of the teaching module were interactive. The teaching module was packaged with an attractive visual design and systematic layout, the integration of verses from the Qur’an and Hadith related to the human reproductive system, and the presence of special features such as Islamic Values and Critical Thinking designed to stimulate students’ critical thinking skills so that students were interested in reading it. The validity value of the teaching module was declared very valid based on the assessment of media experts at 93.80% and material experts at 97.04%. The practicality value of the teaching module was declared very practical based on the teacher’s assessment at 89.24% and the student’s assessment at 85.69%. The value of increasing students’ critical thinking skills was analyzed through N-Gain analysis per indicator with an average result of 0.85 (high). It can be conclude that the teaching module has interactive.